The Readiness of Private Higher Education Institutions in Indonesia to Adopt Blockchain Technology in Accounting Information Systems - Rani, Ratih Hayu; Pratolo, Suryo (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2024)
This study aims to evaluate the readiness of Private Higher Education Institutions (HEI) in Indonesia to adopt blockchain technology. Using the Unified Theory of Acceptance and Use of Technology (UTAUT) model, this research explores the factors influencing the acceptance of blockchain technology, including Relative Advantage, Accounting Information Quality, Trust, Performance Expectancy, Effort Expectancy, and Intention to Use. Blockchain, as a decentralized, transparent, and secure technology, has the potential to enhance the accounting systems in Private HEIs. However, the adoption of this technology in the education sector remains at an early stage. This study uses a quantitative approach, with surveys distributed through questionnaires to financial department heads in accredited Private HEI across Indonesia. The findings show that Relative Advantage and Accounting Information Quality have a significant positive impact on Performance Expectancy, while Trust strongly influences Effort Expectancy. Performance Expectancy and Effort Expectancy contribute to the Intention to Use blockchain in Private HEI. This study contributes to the literature on blockchain adoption, particularly in the context of higher education, by emphasizing the potential of this technology to create more efficient, transparent, and secure accounting systems in Private HEI. These findings aim to provide practical guidance for higher education institutions and stakeholders in preparing for successful blockchain implementation.